2018
DOI: 10.24840/2183-6493_002.003_0002
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Critical Orientation of Seismic Loading in 3D Buildings: Preliminary Results for Constant Lateral Forces

Abstract: The angle of seismic excitation has been proven to be an important factor when analysing the 3D behaviour of buildings. However, modern earthquake-related standards only cover partially the effects of this factor and practicable results of relevant studies are still limited. The proposed paper focuses on the determination of the critical angle of incidence based on the building's structural characteristics. An analytical expression is developed to define the critical angle for the case of single storey buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…While previous research has primarily focused on the implications of structural geometrical factors, seismic characteristics, and numerical modeling techniques for the seismic fragility evaluation of geometrically curved bridges, the influence of the seismic excitation direction has rarely been considered. Previous studies have reported that the critical seismic behavior of buildings is strongly influenced by the orientation of the seismic excitation (Skoulidou and Romão, 2016). Several studies have investigated the effect of the loading direction on the dynamic characteristics of geometrically straight bridge structures.…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has primarily focused on the implications of structural geometrical factors, seismic characteristics, and numerical modeling techniques for the seismic fragility evaluation of geometrically curved bridges, the influence of the seismic excitation direction has rarely been considered. Previous studies have reported that the critical seismic behavior of buildings is strongly influenced by the orientation of the seismic excitation (Skoulidou and Romão, 2016). Several studies have investigated the effect of the loading direction on the dynamic characteristics of geometrically straight bridge structures.…”
Section: Introductionmentioning
confidence: 99%